An integrative approach to strength and neuromuscular power training for basketball - Schelling, X.; Torres-Ronda, L. (Strength and Conditioning Journal, 2016)
Basketball players achieve excellence by fitness levels, sport-specific skills, and decision making. In this article, the authors present a strength and neuromuscular power training methodology, which integrates the latest scientific knowledge on strength training, suggests a practical, integrative, specificity-based methodology covering player development from the weight room to the court, and involves all the staff members around the basketball player to optimize his/her preparation.